ChemInform Abstract: Synthesis of MacMillan Catalyst Modified with Ionic Liquid as a Recoverable Catalyst for Asymmetric Diels—Alder Reaction. Issue 43 (October 2015) - Chauhan, ManMohan Singh; Kumar, Pramod; Singh, Surendra
Abstract The catalyst can be recovered and reused up to five cycles with only a slight decrease in enantiomeric excess and product conversion.